MATERNAL AND NEONATAL OUTCOMES FOLLOWING VAGINAL PROGESTERONE TREATMENT IN TWIN PREGNANCIES: A COHORT STUDY (The Research of Medical Science Review, 2024)
This cohort study evaluates maternal and neonatal outcomes following vaginal progesterone treatment in twin pregnancies at Swat Medical College and Allied Teaching Hospitals, Saidu Shareef, Swat, from January 2022 to June 2024. A total of 300 women with twin pregnancies received either standard care or additional vaginal progesterone, and outcomes were assessed based on preterm birth rates, neonatal morbidity, and maternal complications. Results indicated that progesterone treatment was associated with a significant reduction in preterm births (p < 0.05) and improved neonatal outcomes, including lower rates of respiratory distress and NICU admissions. Maternal outcomes, such as incidence of gestational hypertension and preeclampsia, showed no significant differences between groups. Findings suggest that vaginal progesterone may be beneficial in reducing preterm birth risk in twin pregnancies, with positive implications for neonatal health. Further research is recommended to validate these findings and assess long-term effects on neonatal outcomes